This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: t = 3 / ( v ) . For any time afterwards, v = 0 , so x stays constant at 1 / . Thus, x ( t ) = ( 1 1-(1-1 3 v t ) 3 ) , for t 3 v 1 , for t > 3 v (b) From previous part, x max = 1 . (c) As t , the velocity will reach the terminal velocity, regardless of v . When v = v term = terminal velocity, the acceleration is zero, so we have m dv dt = 0 = K-b v term , or v term = K 2 b 2 . 2...
View Full Document